Localizing-ground Transmitters Using Airborne Antenna Array - Daffalla, Mirghani Moutaman (2020)
A Master of Science thesis in Mechatronics Engineering by Mirghani Moutaman Daffalla entitled, “Localizing-ground Transmitters Using Airborne Antenna Array”, submitted in December 2020. Thesis advisor is Dr. Hasan Mir and thesis co-advisors are Dr. Mamoun Abdel-Hafez and Dr. Nasser Qaddoumi. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).